KAJIAN FILSAFAT HUMANISME DALAM PEMBENTUKAN KARAKTER ATLET MAHASISWA - Radhika Putri; Damanik, Gleadys Trieuniqe; Barus, Daniel Pirmana; Manalu, Marudut Royto; Barus, Ekyanto Baresta; Nurkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of modern sports increasingly emphasizes not only physical achievement but also the formation of strong character among athletes. Student athletes, as individuals who simultaneously engage in academic and athletic activities, face various challenges related to discipline, responsibility, integrity, and sportsmanship. The increasing orientation toward competition and achievement has raised concerns regarding the decline of moral and ethical values in sports. Therefore, a philosophical approach is needed to strengthen character development through values that prioritize human dignity and personal growth. This study aims to examine the role of humanistic philosophy in shaping the character of student athletes. The research employs a literature review method by analyzing various scientific publications, books, and academic sources related to humanism, character education, and sports philosophy. The findings indicate that humanistic philosophy provides a conceptual foundation for developing student athletes through values such as responsibility, honesty, empathy, self-actualization, discipline, and respect for others. Keywords: Humanism Philosophy, Character Building, Student Athletes, Sports Ethics, Higher Education